Distribution of Cytoglobin in the Mouse Brain - Reuss, Stefan; Wystub, Sylvia; Disque-Kaiser, Ursula; Hankeln, Thomas; Burmester, Thorsten (Frontiers in Neuroanatomy, 2016)
Cytoglobin (Cygb) is a vertebrate globin with so far poorly defined function. It is expressed in the fibroblast cell-lineage but has also been found in neurons. Here we provide, using immunohistochemistry, a detailed study on the distribution of Cygb in the mouse brain. While Cygb is a cytoplasmic protein in active cells of the supportive tissue, in neurons it is located in the cytoplasm and the nucleus. We found the expression of Cygb in all brain regions, although only a fraction of the neurons was Cygb-positive. Signals were of different intensity ranging from faint to very intense. Telencephalic neurons in all laminae of the cerebral cortex, in the olfactory bulb (in particular periglomerular cells), in the hippocampal formation (strongly stained pyramidal cells with long processes), basal ganglia (scattered multipolar neurons in the dorsal striatum, dorsal and ventral pallidum), and in the amygdala (neurons with unlabeled processes) were labeled by the antibody. In the diencephalon, we observed Cygb-positive neurons of moderate intensity in various nuclei of the dorsal thalamus, in the hypothalamus, metathalamus (geniculate nuclei), epithalamus with strong labeling of habenular nucleus neurons and no labeling of pineal cells, and in the ventral thalamus. Tegmental neurons stood out by strongly stained somata with long processes in, e.g., the laterodorsal nucleus. In the tectum, faintly labeled neurons and fibers were detected in the superior colliculus. The cerebellum exhibited unlabeled Purkinje-neurons but signs of strong afferent cortical innervation. Neurons in the gray matter of the spinal cord showed moderate immunofluorescence. Peripheral ganglia were not labeled by the antibody. The Meynert-fascicle and the olfactory and optic nerves/tracts were the only Cygb-immunoreactive fiber systems. Notably, we found a remarkable level of colocalization of Cygb and neuronal nitric oxide-synthase in neurons, which supports a functional association.